Into the vault of the Vavilov wheats: old diversity for new alleles - Riaz, Adnan; Hathorn, Adrian; Dinglasan, Eric; Ziems, Laura; Richard, Cecile; Singh, Dharmendra; Mitrofanova, Olga; Afanasenko, Olga; Aitken, Elizabeth; Godwin, Ian; Hickey, Lee (Genetic resources and crop evolution, 2017)
Intensive selection in wheat ( Triticum aestivum L.) breeding programs over the past 100 years has led to a genetic bottleneck in modern bread wheat. Novel allelic variation is needed to break the yield plateau, particularly in the face of climate change and rapidly evolving pests and pathogens. Landraces preserved in seed banks likely harbour valuable sources of untapped genetic diversity because they were cultivated for thousands of years under diverse eco-geographical conditions prior to modern breeding. We performed the first genetic characterisation of bread wheat accessions sourced from the N. I. Vavilov Institute of Plant Genetic Resources (VIR) in St Petersburg, Russia. A panel comprising 295 accessions, including landraces, breeding lines and cultivars was subject to single seed descent (SSD) and genotyped using the genotyping-by-sequencing Diversity Arrays Technology platform (DArT-seq); returning a total of 34,311 polymorphic markers (14,228 mapped and 20,083 unmapped). Cluster analysis identified two distinct groups; one comprising mostly breeding lines and cultivars, and the other comprising landraces. Diversity was benchmarked in comparison to a set of standards, which revealed a high degree of genetic similarity among breeding material from Australia and the International Maize and Wheat Improvement Center (CIMMYT). Further, 11,025 markers (1888 mapped and 9137 unmapped) were polymorphic in the diversity panel only, thus representing allelic diversity potentially not present in Australian or CIMMYT germplasm. Open-access to DArT-seq markers and seed for SSD lines will empower researchers, pre-breeders and breeders to rediscover genetic diversity in the VIR collection and accelerate utilisation of novel alleles to improve wheat.